Prediction of Development of Critical Limb Ischemia in Hemodialysis Patients. Issue 4 (25th March 2015) - Yoshikawa, Hisao; Iijima, Raisuke; Hashimoto, Go; Hara, Hidehiko; Omae, Kiyotsugu; Yoshikawa, Yumiko; Suzuki, Makoto; Nakamura, Masato; Sugi, Kaoru; Yoshikawa, Masao
Abstract Hemodialysis (HD) patients with critical limb ischemia (CLI) suffer chronic inflammation and repeated infection, require intervention, and may have a protracted hospital stay. Therefore, early prediction is particularly important for management of CLI in patients with suspected peripheral artery disease. The purpose of this study is to develop a simple score for predicting the incidence of CLI in HD patients with suspected peripheral artery disease. The subjects were 139 asymptomatic patients receiving maintenance HD and with ABI <1.0. Multivariate logistic regression analysis was used to identify factors associated with development of CLI. These factors were subsequently weighted and integrated into a scoring system for the prediction of onset of CLI. Twenty‐five patients had onset of CLI. Five factors selected from the multivariate model were weighted proportionally using their respective odds ratio (OR) for incidence of CLI (history of cerebral vascular disease, OR 6.42 [3 points]; diabetes, OR 3.92 [2 points]; hypoesthesia, OR 4.21 [2 points]; left ventricular ejection fraction <50%, OR 3.89 [2 points]; serum albumin <3.5 g/dL, OR 4.39 [2 points]). Three strata of risk were defined (low risk, 0 to 3 points; intermediate risk, 4 to 6 points; and high risk 7 to 11 points) with excellent prognostic accuracy for progression to CLI using the Kaplan–Meier method. Five factors were identified that increased the risk of progression to CLI in HD patients with suspected peripheral artery disease. A combination of those factors permitted establishment of three risk strata for accurate prediction of onset of CLI.